Video Game Art Reader Volume 4 - Funk, Tiffany (Amherst College Press, 2022)
In computing, overclocking refers to the common practice of increasing the clock rate of a computer to exceed that certified by the manufacturer. The concept is seductive but overclocking may destroy your motherboard or system memory, even irreparably corrupt the hard drive. Volume 4 of the Video Game Art Reader (VGAR) proposes overclocking as a metaphor for how games are produced and experienced today, and the temporal compressions and expansions of the many historical lineages that have shaped game art and culture. Contributors reflect on the many ways in which overclocking can be read as a means of oppression but also a strategy to raise awareness of how inequities have shaped video games.